THE EFFECT OF MOON PHASES ON CRAB (Portunus pelagicus) CATCHES IN MUNDU DISTRICT, CIREBON REGENCY, WEST JAVA - Zaidy, Azam Bachur; Rosadi, Rosadi; Asnawi, Asnawi; Nurmalia, Nayu; Kamsiah, Kamsiah (Jurnal Perikanan Unram, 2025)
Crab is a marine commodity with a relatively expensive price, but the catch is often uncertain. Crab like crustaceans in general are positively phototactic, which naturally in the sea the activity of crabs at night is influenced by the moon phase. This study aims to determine the effect of the moon phase on the catch of fishermen in Mundu District, Cirebon Regency, West Java. The study used the Completely Randomized Design (CRD) method with 4 treatments, namely the time of capture on the 5th, 15th, 21st and 29th of Hijriah, crab catch data were collected from 5 fishing boats in each treatment/moon phase. The same boat was used in each moon phase. In addition, a study was conducted on the effect of fishing costs on catches. The results showed that the crab catch on the 15th of Hijriah (full moon) was the highest at 9.6 kg, followed by the 5th of Hijriah 8.6 kg, the 30th of Hijriah 6.8 and the lowest catch on the 21st of Hijriah 6.6 kg. The results of the regression analysis show that the variable of fishing costs does not have a significant effect on crab catches. The results of this study can be used by fishermen in planning crab catching activities.